CONTOURS OF CHANGE: FEMALE (DIS) EMPOWERMENT AND SELF-REINVENTION IN THE LOWLAND - Chandel, Priyanka Singh; Pandey, S.N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Contours of Change follow the experience of Gauri, Jhumpa Lahiri's first-generation female heroine, through migration and cultural transition. Set in the politically heated milieu of 1960s Kolkata, the story tracks Gauri's development as she navigates the unsettling repercussions of her move from India to the United States. Gauri defies traditional gender stereotypes in her quest of intellectual independence and personal autonomy, making bold decisions that both empower and alienate her. This study digs into the complex dynamics of female empowerment, (dis)empowerment, and self-reinvention in the context of migration, examining transcultural transformations and tensions between individual identity and cultural memory. Gauri's journey emphasizes the contrasts inherent in her change, providing a lens through which we may better grasp the broader themes of identity and agency in the diasporic experience.